The Implementation of Flipped Classroom Model with Self-regulated Learning (SRL) on Learning Results for Studying Physics Material - Nurwulandari, Nira (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2024)
The Flipped Classroom is a variation of the learning model that can be given to students. This experiment describes the impact of providing a Flipped Classroom model with a Self Regulated Learning (SRL) strategy on students' learning outcomes. This research uses a quasi-experiment type with a one-group pre-test and post-test design. The sample was selected using a random sampling technique. This experiment details that applying the Flipped Classroom model with the SRL strategy has an impact on improving learning outcomes. The research results found that the average score for studying Physics Material on the pre-test was 53.00, while it increased to 76.50 on the post-test. This comparison is descriptively shown by a significant increase in understanding of the material after implementing this learning model. This study uses a paired sample t-test, and it was found that there was a significant increase in learning outcomes in the Study of Physics Material. These findings confirm that applying the Flipped Classroom model with the SRL strategy quantitatively improves learning outcomes in the Study of Physics Material and creates interactive learning. Active involvement of students in the learning process has an impact on increasing cognitive abilities, according to Bloom's Taxonomy (revised edition). Studying Physics material using the Flipped Classroom with the SRL strategy can improve learning outcomes and create more effective and interactive learning experiences.